Effects of Utilising Museums in pre-school education - (:unkn) unknown (Common Ground Research Networks, 2011)
This research has been supported by Marmara University Scientific Research Project Committee under project number EGT-C-YLP-171108-0271. The research aimed to investigate the effects of "Programme on Utilising Museums in Pre-School Education" which was carried out according to the social-emotional and cognitive field gains determined by the education program of Ministry of Education on 6 year-old children continuing to pre-school educational institution. In the study both the quantitative and the qualitative data collecting methods were utilized and among experimental design methods pre-test, post-test controlling group design was used. The experimental process was completed in 11 weeks. As conclusion of the research, there is a significant difference in favour of the experimental group, who were involved in the activities of before visit, visit and after visit that took place in the "Programme on Utilising Museums in Pre-School Education" in order to actualize scheduled museum visits, in social-emotional and cognitive improvement, the lastingness of the learned information and the reflection of the museum experience to students' life when compared to the control group of students who were involved in the conventional education. © Common Ground, Hande Usbaş, Oya Abaci, All Rights Reserved.
Keywords: Museum; Museum education; Pre-school education